Peculiarities of excitonic energy transfer at the distance variation between J-aggregates and exciton traps - Sorokin, A.V.; Ropakova, I.Yu.; Borovoy, I.A.; Yefimova, S.L.; Malyukin, Yu.V. (Functional Materials, 2018)
Molecular aggregates called J-aggregates are excitonic systems which could be used as optical antennas. Preliminary experiments demonstrated an effective resonance energy transfer from J-aggregates to other dyes playing role of exciton traps by Forster mechanism. In the present study we report unexpected behavior of the distance dependence of the energy transfer in J-aggregate-exciton trap system. Contrary to typical Forster energy transfer dependence as ~ d⁻⁶, the trap sensitized luminescence reveals nonmonotonic dependence with a maximum at ~ 10 nm distance between the J-aggregates and the exciton traps.